ANALYSIS OF THE MARKETING MIX ON THE DECISION OF STUDENTS IN OPTING THE D3 ACCOUNTING STUDY PROGRAM IN STATE POLYTECHNIC OF BANJARMASIN - Qolbiah, Nurul (INTEKNA informasi teknik dan niaga, 2015)
D3 Accounting Study Program is one of study programs under the School of Accounting in Banjarmasin State Polytechnic.Â  In the last 2 (two) years, the number of students of this Study Program decreased. This was partly due to the opening of the D3 Study Program of Computerized Accounting since the year 2014. Hence, the D3 Accounting Study Program was required to always improve its quality by among others by using the analysis of marketing mix related to educational servicesThis study aimed to analyze the influence of the marketing mix (product, price, place, promotion, people, process, and physical evidence) onthe decision of students in opting the D3 Accounting Study Program. The influence was analyzed both partially and simultaneously. The respondents involved in this study were 146 students. The method used was non-probability sampling i.e. accidental sampling. Data were collected by spreading questionnaires and method of analysis was conducted by multiple linear regression using SPSS software.Theregression test results indicated that the variables of products, people and physical evidence significantly influenced the decision of students in opting the D3 Accounting Study Program. On the other hand, the variables of price, location, promotion, and process did not substantially influence the decision. The variables of product, price, place, promotion, people, process, and physical evidence simultaneously influenced the decision significantly